Prognostic Value of CXCL12 in Non-Small Cell Lung Cancer Patients Undergoing Tumor Resection - Yurie Kogue; Hiroyasu Kobayashi; Yutaka Nakamura; Takatsugu Takano; Chihiro Furuta; Osamu Kawano; Taro Yasuma; Tadashi Nishimura; Corina N. D'Alessandro-Gabazza; Hajime Fujimoto; Esteban C. Gabazza; Tetsu Kobayashi; et al. (MDPI AG, 2023)
Adjuvant chemotherapy is commonly indicated in lung cancer patients undergoing surgical therapy because tumor recurrence is frequent. A biomarker that can predict tumor recurrence in the postoperative period is currently unavailable. CXCR4 receptor and its ligand CXCL12 play important roles in metastasis. This study investigated the value of tumor CXCL12 expression to predict prognosis and indicate adjuvant chemotherapy in non-small cell lung cancer patients. This study enrolled 82 non-small cell lung cancer patients. The expression of CXCL12 was evaluated by immunohistochemistry. The degree of CXCL12 expression was assessed using the Allred score system. Among all subjects, the progression-free survival and overall survival were significantly prolonged in cancer patients with low tumor expression of CXCL12 compared to patients with high tumor expression. Multivariate analysis showed that the increased level of CXCL12 is a significant predictor of progression-free survival and overall survival in NSCLC patients. Among subjects with high tumor CXCL12 expression, progression-free survival and overall survival were significantly improved in patients treated with adjuvant chemotherapy compared to untreated patients. These results suggest the potential value of tumor CXCL12 expression as a marker to predict prognosis and to indicate adjuvant chemotherapy after surgical tumor resection in non-small cell lung cancer patients.